Implementasi Metode Brainstorming Pada Pembelajaran Fikih untuk Mengembangkan Pemikiran Kritis Siswa di MA Terpadu Nurul Anwar - Agus Sulthoni Imami; Siti Maryam; M. Mahbubi (ANSIRU PAI : Pengembangan Profesi Guru Pendidikan Agama Islam, 2025)
Fiqh learning in educational institutions has an important role in shaping students' understanding of Islamic sharia law which is sourced from the Qur'an and Hadith. However, in practice, learning of fiqh is still theoretical and does not provide enough space for students to think critically. Therefore, it is important to have a learning method that can support students to develop their mindset to be able to understand fiqh learning more quickly. One of the methods used in this study is the brainstorming method with descriptive qualitative research. This brainstorming method is a learning technique that encourages students to be more effective in the teaching and learning process where students can develop their thinking that is more analytical and reflective in understanding the concept of fiqh. This method emphasizes more on open discussion and free exploration of ideas. The implementation of this method aims to encourage students to be more active in asking questions, expressing opinions, and analyzing various views of Islamic sharia law. Thus, students can develop critical thinking skills that enable them to understand, evaluate and apply the concept of fiqh in everyday life. This study will analyze the implementation of the brainstorming method in MA Terpadu Nurul Anwar, examine how the process of implementing the method contributes to developing students' critical thinking skills in fiqh learning, and explore the factors that support and hinder the success of implementing the method. It is hoped that the results of this study can contribute to the development of fiqh teaching methods that are more innovative, interactive, and relevant to the needs and characteristics of students.